Cauda Equina Atrophy in Amyotrophic Lateral Sclerosis on Routine Lumbar Magnetic Resonance Imaging. Issue 6 (28th November 2022) - Matsushima, Satoshi; Omoto, Shusaku; Shimizu, Tetsuya; Baba, Akira; Ojiri, Hiroya
Abstract : Objective: The aim of the study was to evaluate the cross-sectional area of the cauda equina in amyotrophic lateral sclerosis (ALS) on routine lumbar magnetic resonance imaging and investigate the diagnostic accuracy in comparison with age- and sex-matched non-ALS controls. Methods: This retrospective study included 15 ALS patients and 15 age- and sex-matched non-ALS controls. Two independent neuroradiologists measured and compared the total cross-sectional area of the cauda equina of ALS patients and the non-ALS controls at the level of the L3 and L4 using axial T2-weighted images. The cutoff value, sensitivity, specificity, and area under the curve were measured. The interobserver reproducibility of the 2 independently obtained measurements was evaluated. Results: The total cross-sectional area of the cauda equina in the ALS group was significantly smaller than that in the non-ALS group (L3: median, 66.73 vs 90.19 mm 2, P < 0.001; L4: median, 52.9 vs 67.63 mm 2, P < 0.001). The cutoff values at L3 and L4 were 76.95 and 61.04 mm 2 with a sensitivity and specificity of 1 and 0.87 and 0.8 and 0.87, respectively. The area under the curve at L3 and L4 were high at 0.96 and 0.94, respectively. The interobserver reproducibility was 0.88 at L3 and 0.89 at L4. Conclusions: The ALS patients showed significant atrophy of the cauda equina compared with non-ALS patients.